Pengaruh latihan imagery terhadap latihan shooting pada Atlet Petanque Kabupaten Bekasi - Angga Wijaya; Tatang Iskandar; Rasyono Rasyono (Motion: Journal Research of Physical Education, 2023)
This research is motivated by the inconsistency of the athlete's shooting ability due to the lack of athlete's confidence during the match. This study aims to determine the effect of imagery training on shooting results at Petanque Athletes in Bekasi. The method used in this study was an experiment with a "two group pretest posttest design". The test instruments in this study were Shot One Targets with a distance of 6, 7 and 8 meters. Sampling used the "Systematic-Sampling" technique with a total of 14 athletes. The treatment in this research is external imagery and internal imagery training. In external imagery training, athletes are assisted by classical music by Ludwig Van Biethoven entitled Symphony and Fur Elise. Whereas in internal imagery training, the athlete performs imagery directly at the training ground while doing drill shooting with one ball target being the target. The test results showed that the average pretest using imagery training was 6.86 and the posttest result was 9.86, an increase of 3.00. While the average result of the pretest without using imagery training was 6.86, and the posttest result was 8.00, an increase of 1.14. The average difference in the increase in shooting results with imagery training and without imagery training is 1.86. Based on the analysis of data processing, it can be interpreted that there is a significant influence of training imagery on shooting results for Petanque Athletes in Bekasi.